1999
DOI: 10.1136/fn.81.3.f168
|View full text |Cite
|
Sign up to set email alerts
|

Blood pressure standards for very low birthweight infants during the first day of life

Abstract: Blood pressures during the first day of life were measured prospectively in 61 very low birthweight infants using umbilical or peripheral arterial lines. Video recordings of real time waveforms were reviewed. Blood pressure correlated linearly with birthweight and gestation. Comparison with available standards showed that infants weighing under 800 g had lower acceptable mean arterial pressure (MAP). The lower limits of MAP for infants between 26 to 32 weeks of gestation were numerically similar to the gestati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
63
0
2

Year Published

2002
2002
2023
2023

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 113 publications
(69 citation statements)
references
References 6 publications
3
63
0
2
Order By: Relevance
“…In the absence of reliable normative data, clinicians have resorted to nonvalidated generalizations, such as assuming that MAP (in Torr) if equated numerically to GA (in weeks) represents the lower limit of normal. 29,30 Poor definition of GA, varying postnatal age at the time of MAP reading, and a wide range of values among infants never treated for hypotension weaken these assumptions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the absence of reliable normative data, clinicians have resorted to nonvalidated generalizations, such as assuming that MAP (in Torr) if equated numerically to GA (in weeks) represents the lower limit of normal. 29,30 Poor definition of GA, varying postnatal age at the time of MAP reading, and a wide range of values among infants never treated for hypotension weaken these assumptions.…”
Section: Discussionmentioning
confidence: 99%
“…21 -23,30 Our group of large discordant twins had higher MAPs than their small discordant counterparts. It has been noted 14,23,30 that among infants of the same birth weight, those with more advanced GA will have higher MAP. This observation is also validated by the fact that small concordants who had similar birth weight but younger GA had lower MAP than small discordant ELBW infants.…”
Section: Cordero and Johnsonmentioning
confidence: 99%
“…Many clinicians now consider a mean arterial pressure (in torr) less than the gestational age (in weeks) as an indication to treat for hypotension. 22,23 Our study focused only on singletons mainly because the arterial pressure is also complicated by several other factors associated with multiple gestations. 7,8 Previous studies have demonstrated that arterial blood pressure in newborns is influenced by birth weight, 3,24 -26 gestational age, antenatal steroid exposure, 4 multiple gestations, 7,8 postnatal age 27,28 and maternal age.…”
Section: Discussionmentioning
confidence: 99%
“…Arterial pressure was measured directly through an indwelling catheter or noninvasively by the oscillometric method. Under unit protocol, any recorded mean arterial pressure less than the gestational age in weeks in the first 24 h of life 22,23 requiring fluid therapy generated a 'hypotension' problem in an infant's NeoData medical record documentation system. Other demographic, diagnostic, therapeutic and outcome data were extracted from NeoData archives.…”
Section: Methodsmentioning
confidence: 99%
“…Both the definition and treatment of hypotension are controversial in ELBW infants, but we felt that this was the best available methodology at the time of study design. 28,29 Since blood pressure is dependent upon gestational and postnatal age, 30,31 defining normal blood pressure using distributions of values in populations is problematic. This is especially true when standards for all premature infants are applied to ELBW infants, because published studies generally include few infants at very early gestations and extremely low birth weights.…”
Section: Discussionmentioning
confidence: 99%